Conflicting values in organizations: local versus intruder managerial values / Boufeldja Ghiat - Ghiat, Boufeldja (Universiti Teknologi MARA Selangor, 2020)
Developing countries are making great efforts to break out the cycle of underdevelopment, relying on a strategy of importing technology and management methods from Western countries. However, this did not produce the desired results, which pushed for the study of the reasons for this problem. The researcher has relied on collecting data for this paper through his past experiences in production and service enterprises. Several visits were carried out to enterprises and interviews were carried out with workers, supervisors, and managers, which led to the conclusion of the importance of cultural values in organizations. The divergence between imported management methods and the lack of training about managing cultural values are among the most critical obstacles to effective human resources management.